I2-promoted tandem cyclization to synthesize polysubstituted pyrano[3, 2-c]chromene-2, 5-diones. Issue 51 (20th December 2019) - Cai, Qun; Zhuang, Shiyi; Yang, Mian; Peng, Na; Liu, Yi; Wu, Anxin
Abstract: An efficient and convenient method for the synthesis of various substituted pyrano[3, 2- c ]chromene-2, 5-diones was developed via the I2 -promoted tandem cyclization of commercially available aryl methyl ketones and 4-hydroxycoumarins. Preliminary mechanism studies indicated that the reaction involved a consecutive iodination/Kornblum oxidation/annulation process. HI produced in the I2 -DMSO system acted as an important promoter, accelerating the annulation protocol. Graphical abstract: Image 1 Highlights: 26 polysubstituted pyrano[3, 2- c ]chromene-2, 5-diones were synthesized via the I2 -promoted tandem cyclization. A consecutive iodination/Kornblum oxidation/annulation process has been proposed as the possible mechanism. HI produced in the I2 -DMSO system acted as a promoter, accelerating the annulation protocol.